2017
DOI: 10.1124/dmd.116.074294
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Prediction of Human Renal Clearance and Drug-Drug Interactions of Organic Anion Transporter Substrates Using In Vitro Transport Data: A Relative Activity Factor Approach

Abstract: Organic anion transporters (OATs) are important in the renal secretion, and thus, the clearance, of many drugs; and their functional change can result in pharmacokinetic variability. In this study, we applied transport rates measured in vitro using OAT-transfected human embryonic kidney cells to predict human renal secretory and total renal clearance of 31 diverse drugs. Selective substrates to OAT1 (tenofovir), OAT2 (acyclovir and ganciclovir), and OAT3 (benzylpenicillin, oseltamivir acid) were used to obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
132
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(141 citation statements)
references
References 44 publications
4
132
0
Order By: Relevance
“…For pemetrexed, a small relative activity factor (RAF) of 5.3 was used, but there were slight differences in methodologies. Others have also reported small RAF values for OAT1 (0.64), OAT2 (7.3), and OAT3 (4.1) …”
Section: Resultsmentioning
confidence: 93%
“…For pemetrexed, a small relative activity factor (RAF) of 5.3 was used, but there were slight differences in methodologies. Others have also reported small RAF values for OAT1 (0.64), OAT2 (7.3), and OAT3 (4.1) …”
Section: Resultsmentioning
confidence: 93%
“…Transport studies using HEK293 cells transfected with renal OATs indicated PF‐04991532 as a substrate to OAT3 but not to OAT1 and OAT2 ( Figure d ). OAT3‐mediated initial uptake clearance was estimated to be ~ 42 μL/minute/10 6 cells from the transfect cell accumulation data using the methodology described by Mathialagan et al …”
Section: Resultsmentioning
confidence: 99%
“…Transporter‐mediated renal secretion was built into the PBPK model. Uptake clearance via OAT3 was obtained from the rate studies using HEK293‐OATs cells (see RESULTS), as previously described . RAF OAT3 of ~ 4.1, which we previously established based on the in vitro – in vivo extrapolation of OAT3‐mediated transport using static model, was initially applied.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations